Platelet aggregation function test for children in order to determine the normative values in different age groups - O. B. Gordeeva; M. S. Karaseva; M. A. Babaikina; N. D. Vashakmadze; M. A. Soloshenko; O. Ya. Smirnova; D. S. Ovchinnikov (Лечащий Врач, 2022)
Mucocutaneous bleeding and thrombocytopenia are commonly encountered in pediatric patients. It is important for pediatricians to recognize when these signs and symptoms warrant further investigation and subsequently what investigations are most helpful and when referral to pediatric hematology is necessary. The most important part of an evaluation for a platelet disorder in a well-appearing child is the history, including family history, and physical examination. Platelet function test for children is a highly demanded investigation. The cornerstone laboratory test is the complete blood cell count. Individual laboratories may vary in their reference ranges for platelet count, but the normal range of platelet count remains 150 to 450 × 109/л. Platelet dysfunction is often not diagnosed, since of throm bocytopathies in most cases do not have clear symptoms, in some cases clinical manifestations of platelet dysfunction are even absent. Meanwhile complete blood count cannot completely reflect changes in the patient's platelet step of hemostasis. For more comprehensive assessment of platelet function in the initial step of the hemostasis it is necessary to evaluate the function of platelets in the whole blood. Whole Blood Impedance Aggregometry measures the change in electrical impedance between two electrodes when platelet aggregation is induced by an agonist. The method is performed using whole blood and so eliminates the need to generate platelet rich plasma. Platelet function testing may have a role to optimize antiplatelet therapy to reduce bleeding and ischemic events. Platelet aggregation function tests with different inductors make it possible to estimate the effectiveness of antiplatelet therapy, select individual doses of drugs and conduct drug monitoring. Platelet aggregation in patients on the antiplatelet therapy is induced by inductors: arachidonic acid (ASPI test), adenosine diphosphate (ADP test) and thrombin (TRAP test). The high prognostic significance of the Impedance Aggregometry results makes it possible to decide on the drug of choice for patients after thrombosis and intravascular interventions, as well as to prevent bleeding during and after surgical procedures.